2016
DOI: 10.1039/c5ee03522h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced UV-light stability of planar heterojunction perovskite solar cells with caesium bromide interface modification

Abstract: Interfacial engineering has been shown to play a vital role in boosting the performance of perovskite solar cells in the past few years. Here we demonstrate that caesium bromide (CsBr), as an interfacial modifier between the electron collection layer and the CH3NH3PbI3−xClx absorber layer, can effectively enhance the stability of planar heterojunction devices under ultra violet (UV) light soaking. Additionally, the device performance is improved due to the alleviated defects at the perovskite-titania heterojun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
422
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 556 publications
(445 citation statements)
references
References 53 publications
14
422
1
3
Order By: Relevance
“…We find the "SPO ratio" is closer to one for doped devices, implying a reduction in the trap-assisted recombination site density. [19] We would expect a lower trap density to also deliver an increase in V oc , which we do not observe in the measured J-V curves. However, in Figure 3b we also show the V oc over measured over time, where we observe that the V oc of the cell containing doped C 60 is higher than the V oc of the control cell.…”
Section: Doi: 101002/adma201604186contrasting
confidence: 51%
See 2 more Smart Citations
“…We find the "SPO ratio" is closer to one for doped devices, implying a reduction in the trap-assisted recombination site density. [19] We would expect a lower trap density to also deliver an increase in V oc , which we do not observe in the measured J-V curves. However, in Figure 3b we also show the V oc over measured over time, where we observe that the V oc of the cell containing doped C 60 is higher than the V oc of the control cell.…”
Section: Doi: 101002/adma201604186contrasting
confidence: 51%
“…[18][19][20] Recently, Yang and co-workers demonstrated that inorganic metal oxides can be employed as interfacial materials to enhance the air stability. [18] Bryant et.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
See 1 more Smart Citation
“…76,77 The control devices, in which the perovskite was coated directly onto TiO 2 , were shown to degrade rapidly which the authors attribute to a UV-induced photo-oxidation process at the TiO 2 surface. 34 This vulnerability to UV-activated degradation processes at the TiO 2 interface was confirmed by Li et al 80 In this study, the authors were able to stabilize the perovskite absorber by inserting a thin layer of CsBr between TiO 2 and the perovskite, thus inhibiting the photocatalytic decomposition of the absorber. 80 Another strategy to impede performance losses due to photoactivated absorber degradation was demonstrated by Pathak et al, who doped the mesoporous TiO 2 2016) layer with aluminum.…”
supporting
confidence: 60%
“…17 Similarly, using cesium bromide (CsBr) and cesium chloride (CsCl) as modifiers, the organo lead halide perovskite-based planar heterojunction solar cells could deliver 16% and 16.8% efficiency with good stability. 18,19 A very recent analysis indicates that this efficiency increases to over 17% with the composition of Cs 0.2 FA 0.8 PbI 2. 84 Br 0.…”
Section: Introductionmentioning
confidence: 99%